2002
DOI: 10.1021/ja0277125
|View full text |Cite
|
Sign up to set email alerts
|

Organometallic Complexes for Nonlinear Optics. 30.1 Electrochromic Linear and Nonlinear Optical Properties of Alkynylbis(diphosphine)ruthenium Complexes

Abstract: A combination of cyclic voltammetry, UV-vis-NIR spectroelectrochemistry, time-dependent density functional theory (TD-DFT), and Z-scan measurements employing a modified optically transparent thin-layer electrochemical (OTTLE) cell has been used to identify and assign intense transitions of metal alkynyl complexes at technologically important wavelengths in the oxidized state and to utilize these transitions to demonstrate a facile electrochromic switching of optical nonlinearity. Cyclic voltammetric data for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
184
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 201 publications
(207 citation statements)
references
References 86 publications
21
184
1
Order By: Relevance
“…The 16-electron species [RuCl(dppe) 2 ]-[PF 6 ] [14] was generated from cis-[RuCl 2 (dppe) 2 ] [15] (1) by chloride abstraction using NaPF 6 and subsequently treated with 4-ethynyl-N,N-diphenylaniline to form the vinylidene complex trans-[Ru(C=CH-4-C 6 H 4 NPh 2 )Cl(dppe) 2 ][PF 6 ] (2, Scheme 1). Deprotonation of 2 by using triethylamine then affords the mono-alkynyl complex trans-[Ru(CϵC-4-C 6 H 4 NPh 2 )Cl(dppe) 2 ] (3), previously prepared in similar yield by direct treatment of 4-ethynyl-N,N-diphenylaniline with 1, without isolation of the intermediate vinylidene complex.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 16-electron species [RuCl(dppe) 2 ]-[PF 6 ] [14] was generated from cis-[RuCl 2 (dppe) 2 ] [15] (1) by chloride abstraction using NaPF 6 and subsequently treated with 4-ethynyl-N,N-diphenylaniline to form the vinylidene complex trans-[Ru(C=CH-4-C 6 H 4 NPh 2 )Cl(dppe) 2 ][PF 6 ] (2, Scheme 1). Deprotonation of 2 by using triethylamine then affords the mono-alkynyl complex trans-[Ru(CϵC-4-C 6 H 4 NPh 2 )Cl(dppe) 2 ] (3), previously prepared in similar yield by direct treatment of 4-ethynyl-N,N-diphenylaniline with 1, without isolation of the intermediate vinylidene complex.…”
Section: Resultsmentioning
confidence: 99%
“…[4] One reason is because oxidation of such compounds can "switch on" absorptions at low energy, thus significantly affecting the third-order NLO behavior. [5][6][7][8][9] We have reported carbonrich organometallics with three accessible redox states as possible multistate linear optical and NLO switches; in particular, we described the introduction of [(η 5 -C 5 Me 5 )(dppe)-Fe(CϵC-4-C 6 H 4 CϵC)Ru(dppe) 2 ] [dppe = 1,2-bis(diphenylphosphanyl)ethane] fragments into both linear and threefold symmetric branched aryleneethynylene architectures; the heterodinuclear fragment permits switching between three states. [10,11] As a continuation of these studies, we now report (i) replacement of the organoiron [Fe(dppe)(η 5 -C 5 HCϵC-4-C 6 H 4 NPh 2 and (HCϵC-4-C 6 H 4 ) 3 N are irreversible processes.…”
Section: Introductionmentioning
confidence: 99%
“…We chose this particular system because it was used in previous conductance measurements 22,23 as a monomer of chains -albeit with different anchor groups -where it was found that depending on the chain length either coherent transport or electron hopping is observed 22 . In addition spectroscopic and quantum chemical studies on similar Ru complexes [24][25][26][27][28] suggest that this molecular species offers the possibility to easily link two carbon-rich chains to each other for the formation of reversible redox systems [29][30][31] with distinct optical transition properties 32,33 , thereby serving as a starting point for the investigation of chains with multiple redox active centers 27 . In contrast to Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of these NLO properties and the demonstrated reversible electrochemical behavior of the Ru-acetylide functions [84] have also been investigated in terms of a possible reversible modulation of the optical properties of these species. The trimeric RuCl species undergoes reversible metal-centered redox processes (Ru II/III ) in solution.…”
Section: Organometallic Fragments In the Dendrimer Backbonementioning
confidence: 99%